The CON−H…+NH2 Blue-Shifting H-Bond Stabilizing Effect on Z Secondary Amides and Cyclic System Conformational Rearrangement through an Alkylamine-Chain Migration Pathway - Jaroslaw Spychala (Journal of Chemistry)
The paper is focusing on the amide linkage exceptional properties and usage of chemistry (conformational rearrangement, geometrical stereoisomers, spectroscopic blue shift phenomenon, protonation and deprotonation reactions, synthetic scope, and mechanistic implications). Hydrogen-bond-stabilized acylation reactions of a diamine with thioamides or nitriles reveal how substituents influence both the outcome of stereoselectivity and interactions. Inferring the chemical mechanism from the structures of reactants is dissimilar to the appropriate E isomers, the Z form becomes more favored in the secondary amides obtained. One conclusion from the estimation of Z structures, based on the 1H-15N 2D NMR spectra in comparison with the references, is the existence of the intramolecular, blue shifting CON−H…+NH2CH3 hydrogen bonds. The rearrangement of a methylamino residue provided the free base stabilized in the CH3N−H…O=CNH after deprotonation. An essential part of the publication describes systems in a highly stereoselective fashion, so the stereochemical outcome of the product is predictable now.